Cyber physical systems : design, modeling, and evaluation : 6th International Workshop, CyPhy 2016, Pittsburgh, PA, USA, October 6, 2016, Revised selected papers /: design, modeling, and evaluation : 6th International Workshop, CyPhy 2016, Pittsburgh, PA, USA, October 6, 2016, Revised selected papers. (2017) - Unknown
No abstract available